1995
DOI: 10.1002/j.1556-6676.1995.tb01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Specialties: A Case of Basic Preparation Rather Than Advanced Specialization

Abstract: This article focuses on many of the issues and questions involved in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is obvious that test takers assume the former, whereas exam developers assert it is the latter. Hosie (1995) noted that certification in a profession means the individual has met a set of minimal standards but does not denote quality of practice. It appears that many examinees disagree with this as the appropriate role of the EPPP, or they also may feel that the EPPP is not representative of minimal standards.…”
Section: Implications and Applicationsmentioning
confidence: 99%
“…It is obvious that test takers assume the former, whereas exam developers assert it is the latter. Hosie (1995) noted that certification in a profession means the individual has met a set of minimal standards but does not denote quality of practice. It appears that many examinees disagree with this as the appropriate role of the EPPP, or they also may feel that the EPPP is not representative of minimal standards.…”
Section: Implications and Applicationsmentioning
confidence: 99%
“…In the past it was argued that a CACREP specialty designation was a specialized curriculum needed for the preparation of substance abuse counselors (Hosie, 1995). Yet, recent research findings, especially those which revealed a recent increase in the demand for substance abuse counselors trained at the master's degree level, made a strong case for the re-examination of the issue (Mustaine, West, & Wyrik, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Although the call for a specialist designation and its accompanying formal preparation for substance abuse counseling has been questioned (Hosie, 1995;Miller & Brown, 1997), a preponderance of studies have shown that specialized graduate-level preparation of substance abuse counselors is needed. The present study examined the perceived need for CACREP-accredited counselor education programs to formalize curriculum standards for substance abuse counseling courses.…”
mentioning
confidence: 99%
“…A curriculum vita is a comprehensive professional biography. It contains a complete personal history with information that may be of interest to employers (Hosie, 1995;Remley, 1995), licensure boards, managed care companies, and so forth (Smith & Robinson, 1995). An abbreviated résumé, usually one to two pages long, is individually designed for a particular purpose.…”
Section: Vita and Résumémentioning
confidence: 99%